Physicians' brain drain: Investigating the determinants to emigrate through empirical evidence - Evgenia Anastasiou; Georgia Anagnostou; George Theodossiou; Vasileios Papamargaritis (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: The economic crisis in Greece has caused widespread suffering both in society and the economy. Among other things, new forms of geographical mobilities emerged highlighting the country's inability to retain a scientifically skilled workforce. One of the most important scientific branches been hit is the medical one. The purpose of this study is to identify the intention as well as the main factors that push young greek physicians to emigrate. Design/methodology/approach: For the present study, a tool for assessing young physicians' perceptions was designed and field research was performed on 239 medical school students and young physicians for up to 39 years. Descriptive and inferential statistical analysis was used to describe the data and generalize the results. Finally, Factor Analysis (Principal Component Analysis) was used to condense the initial variables and capture the determinants in physicians' brain drain. Findings: Young physicians show high intention to seek employment abroad. There are differences between men and women regarding their perceptions of the possible causes of emigration. Women consider more than men that unemployment, employment prospects, and opportunities and quality of life to be the most important reasons in the migratory decision. In addition, the young doctors whose family incomes are either very low or quite high are more receptive to looking for work abroad. Finally, the multivariate analysis highlights four main determinants feeding physicians decision-making; homeland's social identity, lack of prospects, unfavorable economic environment, and continuation of studies. Research limitations/implications: The period of the field research was conducted from September to November 2018. As a result, there are restrictions on whether participants' responses are affected by the economic crisis or not, as Greece in 2018 began to show macroeconomic stability. Originality/value: In the last decade, a large wave of young scientists' emigration has been recorded in Greece. This wave intensified in 2012 and became permanent in the following years, taking on large-scale exodus, with high annual outflows. Brain Drain as an evolving phenomenon has been studied both by the national and international academic community. However, in the case of Greece, the research of perceptions, intentions, and the main reasons for brain drain by medical professionals is limited. The present study seeks to fill the gap found in the literature through field research about the determinants of physicians' brain drain in Greece.
Keywords: J1; J21; J24; J6; O15; 330; Brain Drain; Physicians; Migration; Human Geography; Principal Component Analysis; Greece